[2 + 2] cycloaddition reaction and luminescent sensing of Fe3+ and Cr2O72− ions by a cadmium-based coordination polymer. Issue 32 (22nd July 2019) - Zhu, Rong-Rong; Wang, Tao; Yan, Tong; Jia, Lei; Xue, Zhe; Zhou, Jie; Du, Lin; Zhao, Qi-Hua
Abstract : A cadmium-based coordination polymer can produce the corresponding photoproduct via [2 + 2] cycloaddition reaction, and can detect both Fe 3+ and Cr2 O7 2− ions. Abstract : A new cadmium-based coordination polymer (CP), [Cd3 (bpe)2 (ceba)2 (fa)2 (H2 O)2 ] n (1 ; fa = formate anions), was constructed by solvothermal reactions of cadmium nitrates with trans -1, 2-bis(4′-pyridyl)ethylene ligand (bpe) and 4-(1-carboxy-ethoxy)-benzoic acid (H2 ceba). The [2 + 2] photodimerization reaction of CP1 under UV irradiation generated the corresponding photoproduct [Cd3 ( rctt -tpcb)(ceba)2 (fa)2 (H2 O)2 ] n (1a ; rctt -tpcb = tetrakis(4-pyridyl)-cyclobutane) via a single-crystal-to-single-crystal (SCSC) transformation. Single crystal X-ray diffraction unveiled that CPs1 and1a have similar 2D layered structures, except that rctt -tpcb replaced a pair of bpe ligands in the latter. Furthermore, CPs1 and1a are good bifunctional luminescent sensors that can detect Fe 3+ and Cr2 O7 2− ions in a mixed medium of water and DMF and display high sensitivity, selectivity, and anti-jamming capability for the recognition of Fe 3+ and Cr2 O7 2− ions. Moreover, we also examine in detail the possible luminescent quenching mechanisms of1 and1a toward Fe 3+ and Cr2 O7 2− ions.